Complete blood count variations regarding blood serum tocopherol and age - Cuba Caparó, Alberto (1957)
Successive determinations of tocopherol in blood serum and Complete blood count, practiced in a group of nine normal lambs up to 4,000 meters above sea level; for a period of 240 days, there has been a statistically significant, in the number of erythrocytes, hemoglobin and hematocrit reaches the highest at 60 days old values and coincides with the lowest values tocopherol ds considerable increase blood serum. From this age haematological values decreased progressively, reaching 240 days figures fall within the variation accepted rams high. It suggests that the variations found in the blood cell and serum tocopherol box in relation to age, are physiological.